E-Court dan Keadilan Prosedural: Studi Empiris Perspektif Hakim Indonesia - Adinda Ratih, Soleh (LPPM Universitas Sains dan Teknologi Komputer, 2025)
The rapid digital transformation in the judicial sector has brought significant changes to procedural justice, particularly through the implementation of electronic courts (e-courts) in Indonesia. This study explores how judges perceive and apply procedural justice principles in digital trials. Using a qualitative research design with an empirical approach, data were collected through in-depth interviews with 25 judges from district and high courts in 12 cities, supported by courtroom observations and document analysis. Thematic analysis identified five major themes: transparency of proceedings, parties’ participation, procedural consistency, technical challenges and digital literacy, and the balance between efficiency and substantive justice. The findings show that while e-court improves administrative efficiency and transparency, it also raises concerns regarding equal participation and substantive fairness due to technological barriers and reduced face-to-face interaction. Nearly one-third of the judges viewed e-court as potentially hindering procedural justice, indicating that digitalization has not yet ensured a uniform perception of fairness. The novelty of this research lies in presenting judges’ empirical perspectives, which remain understudied compared to normative or technical analyses. Academically, this study contributes to the discourse on e-justice in developing countries and, practically, offers policy implications for strengthening digital judicial governance. The findings highlight the need for enhanced judicial training, improved technological infrastructure, and more inclusive guidelines to ensure equitable participation in digital trials. Ultimately, the study emphasizes that the e-court should function not merely as a symbol of modernization but as a genuine instrument of substantive justice.